The OCEAN ICE mooring compilation: a standardised, pan-Antarctic database of ocean hydrography and current time series - Zhou, S.; Dutrieux, P.; Giulivi, C. F.; Jenkins, A.; Silvano, A.; Auckland, C.; Abrahamsen, E. P.; Meredith, M.; Vaňková, I.; Nicholls, K.; Davis, P. E. D.; Østerhus, S.; et al. (Earth Syst. Sci. Data, 2025)
Continuous moored time series of temperature, salinity, pressure and current speed and direction are of great importance for understanding the continental shelf and under-ice-shelf dynamics and thermodynamics that govern water mass transformations and ice melting in and around Antarctic marginal seas. In these regions, icebergs and sea ice make ship-based mooring deployment and recovery challenging. Nevertheless, over decades, expeditions around the fringe of Antarctica sporadically deployed and recovered hundreds of moored instruments, including those facilitated through ice shelves boreholes. These datasets tend to be archived in a wide range of data centres, with, to our knowledge, no clear format standardisation. As a result, systematic analysis of historical mooring time series in the marginal seas is often challenging. Here we present the first version of a standardised pan-Antarctic moored hydrography and current time series compilation, with broad international contributions from data centres, research institutes and individual data owners. The mooring records in this compilation span over five decades, from the 1970s to the 2020s, providing an opportunity for a systematic study of the pan-Antarctic water mass transport and shelf connectivity. As a demonstration of the utility of this compilation, we present spectral analysis of the compiled current velocity time series, which unsurprisingly shows the dominating presence of tidal variability within most records. This component of the variability is fitted using multi-linear regression to tidal frequencies, and the tidal fit is removed from the original time series to leave de-tided variability. Given the limited record durations to months to years, de-tided variability is dominated by synoptic (3–10 d period), intraseasonal (10–80 d) and seasonal (∼6 months–1 year) signals. The spatial distribution of the kinetic energy integrated within frequency bands is presented and discussed within respective regional contexts, and future avenues of research are proposed. This data compilation is assembled under the endorsement of Ocean-Cryosphere Exchanges in ANtarctica: Impacts on Climate and the Earth System (OCEAN ICE) project (https://ocean-ice.eu/, last access: 23 October 2025) funded by the European Commission and UK Research and Innovation. It is available and regularly updated in NetCDF format with the SEANOE database at https://doi.org/10.17882/99922 (Zhou et al., 2024a).
Publisher: Copernicus Publications
Keywords: Sørishavet; database; geofysikk; hydrografi; oseanografi

Basal Melt Rate Variability and Tidal Current Vertical Structure From Observations Beneath Ronne Ice Shelf, Antarctica - Anselin, J.; Nicholls, K. W.; Holland, P. R.; Taylor, J. R.; Østerhus, S.; Makinson, K. (Journal of Geophysical Research: Oceans, 2025)
This study examines the interplay between water column structure, tidal currents, and basal melting at a site beneath Ronne Ice Shelf, using a 3-year data set of oceanographic measurements, and a collocated year-long time series of radar-derived melt rate estimates. Currents at the site are characterized by mixed semidiurnal tides with strong spring-neap variability, superimposed on a nontidal flow. The product of current speed and thermal driving, both measured approximately 19 m from the ice base, explains 88% of the melt rate variability. Although current speed is the dominant driver of this variability, thermal driving also contributes non-negligibly on spring-neap and longer timescales. The semidiurnal tidal ellipses feature marked vertical variations, transitioning from nearly rectilinear in the mid-water column to more circular and clockwise (CW)-rotating near the ice. This depth-dependence of the semidiurnal tide is attributed to the differential influence of boundary friction on the CW and anticlockwise (ACW) rotary components near the critical latitude (where the tidal frequency equals the Coriolis frequency). A theoretical model, which assumes depth-independent eddy viscosity, successfully reproduces the observed 3-year mean vertical structure of the tidal ellipses. Considering the total tidal current rather than individual constituents, ice base friction damps both the time-mean flow speed and the tidal fluctuations, with attenuation varying over the spring-neap cycle, peaking during spring tides. The observed latitude- and time-dependent effects of ice base friction on the barotropic tide are not captured in parameterizations that estimate tide-induced friction velocity by scaling the time-averaged barotropic tidal speed with a constant drag coefficient.
Publisher: John Wiley & Sons, Ltd Article number: e2025JC022524
Keywords: Antarktis; Sørishavet; Weddellhavet; glasiologi; hydrografi; isshelf; oseanografi

Giant iceberg meltwater increases upper-ocean stratification and vertical mixing - Lucas, Natasha S.; Brearley, J. Alexander; Hendry, Katharine R.; Spira, Theo; Braakmann-Folgmann, Anne; Abrahamsen, E. Povl; Meredith, Michael P.; Tarling, Geraint A. (Nature Geoscience, 2025)
Ice-sheet mass loss is one of the clearest manifestations of climate change, with Antarctica discharging mass into the ocean via melting or through calving. The latter produces icebergs that can modify ocean water properties, often at great distances from source. This affects upper-ocean physics and primary productivity, with implications for atmospheric carbon drawdown. A detailed understanding of iceberg modification of ocean waters has hitherto been hindered by a lack of proximal measurements. Here unique measurements of a giant iceberg from an underwater glider enable quantification of meltwater effects on the physical and biological processes in the upper layers of the Southern Ocean, a region disproportionately important for global heat and carbon sequestration. Iceberg basal melting erodes seasonally produced winter water layer stratification, normally forming a strong potential energy barrier to vertical exchange of surface and deep waters, while freshwater run-off increases and shoals near-surface stratification. Nutrient-rich deeper waters, incorporating meltwater loaded with terrigenous material, are ventilated to below this stratification maxima, providing a potential mechanism for alleviating critical phytoplankton-limiting components. Regional historical hydrographic data demonstrate similar stratification changes during the passage of another large iceberg, suggesting that they may be an important pathway of aseasonal winter water modification.
Keywords: Sørishavet; Weddellhavet; biogeokjemi; glasiologi; global oppvarming; hydrografi; klimaendringer; klimatologi; oseanografi

Hydrography and circulation below Fimbulisen Ice Shelf, East Antarctica, from 14 years of moored observations - Lauber, Julius; Hattermann, Tore; de Steur, Laura; Darelius, Elin; Fransson, Agneta (Ocean Sci., 2024)
Future mass loss from the East Antarctic Ice Sheet represents a major uncertainty in projections of future sea level rise. Recent studies have highlighted the potential vulnerability of the East Antarctic Ice Sheet to atmospheric and oceanic changes, but long-term observations inside the ice shelf cavities are rare. Here, we present new insights from observations from three oceanic moorings below Fimbulisen Ice Shelf from 2009 to 2023. We examine the characteristics of intrusions of modified Warm Deep Water (mWDW) across a sill connecting the cavity to the open ocean and investigate seasonal variability of the circulation and water masses inside the cavity using an optimum multiparameter analysis. In autumn, the water below the 345 m deep central part of the ice shelf is composed of up to 30 % solar-heated, buoyant Antarctic Surface Water (ASW), separating colder Ice Shelf Water from the ice base and affecting the cavity circulation on seasonal timescales. At depth, the occurrence of mWDW is associated with the advection of cyclonic eddies across the sill into the cavity. These eddies reach up to the ice base. The warm intrusions are observed most often from January to March and from September to November, and traces of mWDW-derived meltwater close to the ice base imply an overturning of these warm intrusions inside the cavity. We suggest that this timing is set by both the offshore thermocline depth and the interactions of the Antarctic Slope Current with the ice shelf topography over the continental slope. Our findings provide a better understanding of the interplay between shallow inflows of ASW contributions and deep inflows of mWDW for basal melting at Fimbulisen Ice Shelf, with implications for the potential vulnerability of the ice shelf to climate change.
Publisher: Copernicus Publications
Keywords: Dronning Maud Land; hydrografi; isshelf; klimaendringer; klimatologi; oseanografi

Supercooled Southern Ocean Waters - Haumann, F Alexander; Moorman, Ruth; Riser, Stephen C; Smedsrud, Lars H; Maksym, Ted; Wong, Annie P S; Wilson, Earle A; Drucker, Robert; Talley, Lynne D; Johnson, Kenneth S; Key, Robert M; Sarmiento, Jorge L (Geophysical Research Letters, 2020)
In cold polar waters, temperatures sometimes drop below the freezing point, a process referred to as supercooling. However, observational challenges in polar regions limit our understanding of the spatial and temporal extent of this phenomenon. We here provide observational evidence that supercooled waters are much more widespread in the seasonally ice-covered Southern Ocean than previously reported. In 5.8% of all analyzed hydrographic profiles south of 55°S, we find temperatures below the surface freezing point (“potential” supercooling), and half of these have temperatures below the local freezing point (“in situ” supercooling). Their occurrence doubles when neglecting measurement uncertainties. We attribute deep coastal-ocean supercooling to melting of Antarctic ice shelves and surface-induced supercooling in the seasonal sea-ice region to wintertime sea-ice formation. The latter supercooling type can extend down to the permanent pycnocline due to convective sinking plumes—an important mechanism for vertical tracer transport and water-mass structure in the polar ocean.
Keywords: Sørishavet; havis; hydrografi; isbrem; isshelf; oseanografi; polarområdene; sjøis; superkjøling